COMPARATIVE ANALYSIS OF DENTAL IMPLANTS STABILITY - Popovych, I.Yu.; Petrushanko, T.O.; Yeroshenko, G.A.; Steblovskiy, D.V. (World of Medicine and Biology, 2018)
Dental implants are increasingly used in oral surgery. Notwithstanding the advancement of the methods for treatment of caries and its complications, the need of population in implant treatment is increasing annually. Currently, permanent impact of various pathogenic factors (cosmic-planetary, social, physical, chemical and biological) on a human contributes to the occurrence of numerous somatic and dental diseases, including inflammatory-dystrophic periodontal diseases. The most frequent complication of the clinical course of periodontitis is tooth loss as a result of the destructive processes in the osseous tissue of the alveolar ridge. The dentition defects in patients with generalized periodontitis require special management to eliminate them, especially during dental implantation. The paper was aimed at the comparison of the primary and secondary stability of two dental implants, different in design, during the experiment on the porcine jaws with D3-D4 bone density. Based on the studies conducted, it has been proved that one of the main factors affecting the quality of stabilization and osseointegration is the design of the dental implant, which provides the anti-rotational effect, namely the triangular design of the portion of the Alpha Dent Active Bio implant. Dental implants used in the experimental study should be indicated for use in patients with poor bone density of the alveolar ridge of the jaws (D3-D4), which is most often diagnosed during in the development of periodontitis in humans.